PT governments a legacy for the future - Mercadante, Aloizio; Zero, Marceo; Rousseff, Dilma (CLACSO, 2018)
It is used to say that the first victim of a war is the truth. In fact, in a war in the strict sense or in a political war, the murder of the truth and the concealment of the facts occur profusely. It is not different in Brazil. Democracy was neither the first nor the only victim of the parliamentary coup (a.k.a. impeachment) in 2016. It was also the truth. Before the coup, and to justify it, anti-people and anti-national forces broadcasted, to exhaustion, a series of lies about the governments of the Workers Party (PT). The presentation of Dilma Rousseff